2013
DOI: 10.1007/s11517-013-1106-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced regeneration of rabbit mandibular defects through a combined treatment of electrical stimulation and rhBMP-2 application

Abstract: We evaluated the new bone regeneration of a rabbit mandibular defect using hBMSCs under electrical stimulation combined with rhBMP-2 in this study. An inner scaffold prepared by setting a collagen sponge with hBMSCs and hydrogel was placed into a polycaprolactone (PCL) outer box, and an electrical stimulation device was installed between the inner scaffold and the outer box. There were three experimental groups depending on electrical stimulation and application of rhBMP-2. The experimental group was divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…To evaluate the mechanical recovery of bone grafts in rabbit models of segmental radius defects, bending test configurations have been reported ( 53 55 ). Our studies have shown that both three-point bending resulted in similar outcomes when testing the mechanical integrity of rabbit mandible ( 53 ). In agreement with this study, the primary failure mode for bending was a short oblique fracture.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the mechanical recovery of bone grafts in rabbit models of segmental radius defects, bending test configurations have been reported ( 53 55 ). Our studies have shown that both three-point bending resulted in similar outcomes when testing the mechanical integrity of rabbit mandible ( 53 ). In agreement with this study, the primary failure mode for bending was a short oblique fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Defect area to be resected (rectangular shape; 15 mm long, 7 mm high from the mandibular inferior border) was marked on the mandibular bone under the tooth and osteotomized by rotary drilling machine, where alveolar bone with teeth was preserved with continuity with the residual mandibular bone. Because mandibular stabilization with mini-9 plates after the resection of mandibular body including the alveolar bone with teeth was unstable [33], postoperative dislocation of anterior segment with loosening of mini-plates and screws occurred in our previous experiments due to the strong jaw movement. The bioreactors were positioned into the defect side, stabilized with screws on the neighboring mandibular bone (Fig 4), and the electric stimulator with battery coin were implanted at the submandibular area and then the incision sites were sutured layer by layer.…”
Section: Surgical Proceduresmentioning
confidence: 86%
“…Increased calcium level might lead to an increased nitric oxide levels, which acts in a physiological context through increased synthesis of cyclic guanosine monophosphate (cGMP) and subsequent activation of protein kinase G, which was associated with cell division and nucleic acid synthesis [48]. ES also made the cellular environment more suitable for osteogenesis [33]. The effect of ES included increased gene expression of type I collagen and prostaglandin [30], growth factors (BMP-2, IGF-1, VEGF), and chemokines with receptors [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations